1988
DOI: 10.1203/00006450-198803000-00013
|View full text |Cite
|
Sign up to set email alerts
|

The Ontogeny of Pulmonary Defenses: Alveolar Macrophage Function in Neonatal and Juvenile Rhesus Monkeys

Abstract: ABSTRACT. Using the technique of bronchoalveolar lavage, we isolated alveolar macrophages (AM) from the lower respiratory tract of newborn (1-4 days of age), infant (6-10 days of age), juvenile (3-6 months of age), and adult rhesus monkeys. The AM thus obtained were assayed in vitro to determine their chemotactic, phagocytic, and candidicidal capabilities. The predominant (289%) cell type in bronchoalveolar lavage effluent in all ages was the AM. Chemotaxis, phagocytosis, and killing of Candida albicans were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…As predicted by previous studies on AM number after birth (13,17,19), there was an exponential increase in the number of AM during the first postnatal week with a linear increase thereafter to adult levels (Fig. 1).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…As predicted by previous studies on AM number after birth (13,17,19), there was an exponential increase in the number of AM during the first postnatal week with a linear increase thereafter to adult levels (Fig. 1).…”
Section: Resultssupporting
confidence: 65%
“…Through the prior work of several investigators (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), it is known that an influx of AM into the rabbit lung precedes birth by 24 h. This is followed by an exponential increase in AM number during the first week after delivery. During postnatal lung development, there is a gradual shift from a homogeneous, monocyte-like population to a more heterogeneous population of AM of varying density and function (14,(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial functions of AM include phagocytosis, oxidant mediated microbial killing, and the recruitment of leukocytes by pro-inflammatory cytokines. Studies in the rhesus monkey have suggested that AM in the neonatal lung are deficient in a range of antimicrobial activities [4], although no parallel studies have been performed in healthy young children. AM are also important in controlling responses to inhaled antigens.…”
mentioning
confidence: 99%
“…When compared with the adult, the newborn macrophage functions of chemotaxis, phagocytosis, and bacterial killing are diminished (23)(24)(25). GSH is essential for optimal functioning of phagocytic cells, such as the alveolar macrophage.…”
mentioning
confidence: 99%